Moisture Content and Mould Risk in Concrete Outer Walls - Björnsdóttir, Jóhanna Eir; Jóhannsson, Jóhann Björn (KTH, Byggnadsteknik, 2018)
Previous studies on the typical Icelandic external wall have shown thatcondensation occurs at the interior surface of the concrete and field inspectionshave supported this conclusion. The primary objective ofthis study is to analyse the hygrothermal behaviour of the typical Icelandicwall and evaluate the mould risk at the interior surface of theconcrete.A comparative study is performed to compare the hygrothermalperformance and mould growth risk of two concrete outer wall structureswith interior and exterior insulation, by performing a parametricstudy using the simulation program WUFI® Pro.Additional parametric studies are performed in order to analyse theeffect of various material properties of the Icelandic building materialson the hygrothermal behaviour of the wall. This part also utilizedWUFI® Pro.To investigate the thermal bridge of the Icelandic wall, simulationswere conducted with the COMSOL Multiphysics software to evaluatethe linear thermal bridge and the risk of condensation at the joint.Lastly, an experiment was set up at the Innovation Center Iceland tomodel the interior insulated wall-slab section. The experimental setupwas completed during this time but the results will be analysedfurther after the thesis work.The results from this study indicate that the typical Icelandic wall ismore sensitive to rain than to interior moisture load and that no condensationoccurs within the wall structure. As concrete is inorganic,the risk of mould growth in the wall structure is limited, however,with increased driving rain load the mould risk increases. The resultsalso revealed that the moisture content of the interior insulated wallwas a great deal higher compared to the exterior insulated wall. Furthermore,the humidity level at the interior surface of the concrete inthe interior insulated wall exceeded the recommended critical humiditylevel based on general suggestions. Finally, results indicated thatusing a more dense concrete resulted in higher relative humidity at theinterior surface but a lower total water ...